ACTA: The ethical analysis of a failure, and its lessons - Luciano Floridi (European Centre for International Political Economy (ECIPE), 2012)
ACTA (the Anti-Counterfeiting Trade Agreement) was originally meant to enforce and harmonise IPR provisions in existing trade agreements within a wider group of countries. This was commendable in itself, so ACTA's failure was all the more disappointing. In this article, I wish to contribute to the post-ACTA debate by proposing a specific analysis of the ethical reasons why ACTA failed, and what we can learn from them. I argue that five kinds of objections - namely, secret negotiations, lack of consultation, vagueness of formulation, negotiations outside any international body, and the creation of a new governing body outside already existing forums - had only indirect ethical implications. This takes nothing away from their seriousness but it does make them less compelling, because agreements should be evaluated, ethically, for what they are, rather than for the alleged reasons why they are being proposed. I then argue that ACTA would have caused three ethical problems: an excessive and misplaced kind of responsibility, a radical decrease in freedom of expression, and a severe reduction in information privacy. I conclude by indicating three lessons that can help us in shaping ACTA 2. First, we should acknowledge the increasingly vital importance of the framework of implicit expectations, attitudes, and practices that can facilitate and promote morally good decisions and actions. ACTA failed to perceive that it would have undermined the very framework that it was supposed to foster, namely one promoting some of the best and most successful aspects of our information society. Second, we should realise that in advanced information societies, any regulation affecting how people deal with information is now bound to influence the whole "onlife" habitat within which they live. So enforcing IPR becomes an environmental problem. Third, since legal documents, such as ACTA, emerge from within the infosphere that they affect, we should apply to the process itself, which one day may lead to a post-ACTA treaty, the very framework and ethical values that we would like to see promoted by it.
Keywords: 330; Produktpiraterie; Internationales Abkommen